Changes in the flow properties of white blood cells after acute myocardial infarction. Issue 5 (November 1989) - Nash, G B; Christopher, B; Morris, A J; Dormandy, J A
Abstract : Because they can obstruct blood vessels and release noxious substances, white blood cells may contribute to the development of tissue ischaemia. The flow properties of white cells were tested after myocardial infarction, by measuring the filtration rates of cell suspensions through 8 microns pore filters. Compared with mononuclear cells from age matched controls, mononuclear cells from patients with infarction showed impaired filterability within the first day after the onset of pain; this condition persisted for at least two days and by day 10 it was improved. On day 1, granulocyte filterability and the proportion showing morphological evidence of activation were nearly normal. By day 3 the flow resistance and activation had increased, but the changes seen depended on the age of the patient. The filterability and activation of granulocytes from patients aged less than 60 were significantly increased from day 1, whereas there were no changes in granulocytes from patients aged greater than 60 years. Suspensions of unfractionated white cells showed changes intermediate between the mononuclear cells and granulocytes. A group of five patients who presented with chest pain but who were subsequently found not to have had an infarction showed no evidence of abnormal filterability or activation. The changes in filterability probably reflect white cell activation, which may have an adverse effect on the perfusion of the ischaemic myocardium.